Factors Affecting the Financial Literacy During Pandemic - Ari Susanti (Journal of Business and Management Review, 2021)
Insights on literacy during the current pandemic are needed in order to create qualified and financially intelligent individuals or groups that can be used for financial management so that they are beneficial for their lives and able to prosper financially. Financial literacy is an intelligence and understanding of financial institutions, financial products and financial services. Individuals who have good financial literacy will have an awareness of the direction of their financial management goals, thus, they will be smarter in taking action on their assets. Having good financial literacy, a person will have strong abilities in terms of managing finances, financial planning skills, investment insight and knowledge of saving and borrowing, so that individuals will be careful of the assets they have and not easily get trapped into online loans or fake loans detrimental and far from financial well-being. Factors that influence the financial literacy during the pandemic include financial attitude, income and peers. The population taken in this observation was active female students in Surakarta with a total number of 230 respondents. This observation sample was taken using the purposive sampling technique. The data collection technique was done using questionnaires distributed online to respondents and the data analysis of hypotheses testing was done using multiple linear regressions with t test, f test and coefficient of determination through SPSS 21. According to the results of the analysis that has been carried out, it shows that the financial attitude variable has a relevant influence on financial literacy, income has no effect on financial literacy and peers have a relevant influence on financial literacy.